Twinkles, Arthur and Puss - Kerr, Judith (London : HarperCollins Children's Books, 2008)
Twinkles, Arthur, and Puss are three black cats with three different owners, but when the cats do not return from one of their mysterious adventures outside, the owners go off in search of their lost pets.
2.1
K-3
Keywords: Cats -- Juvenile fiction; Cats -- Fiction; Cats -- Fiction